In vivo Analysis of White Adipose Tissue in Zebrafish - Minchin, James E.N. (Methods Cell Biol, 2011)
White adipose tissue (WAT) is the major site of energy storage in bony vertebrates, and also serves central roles in the endocrine regulation of energy balance. The cellular and molecular mechanisms underlying WAT development and physiology are not well understood. This is due in part to difficulties associated with imaging adipose tissues in mammalian model systems, especially during early life stages. The zebrafish (Danio rerio) has recently emerged as a new model system for adipose tissue research, in which WAT can be imaged in a transparent living vertebrate at all life stages. Here we present detailed methods for labeling adipocytes in live zebrafish using fluorescent lipophilic dyes, and for in vivo microscopy of zebrafish WAT.